High detection rates of Torque teno sus virus in co‐infection with important viral pathogens in porcine kidneys on St. Kitts Island, Lesser Antilles. Issue 5 (17th July 2018) - Ghosh, Souvik; Soto, Esteban; Illanes, Oscar; Navarro, Ryan; Aung, Meiji Soe; Malik, Yashpal Singh; Kobayashi, Nobumichi; Fuentealba, Carmen
Abstract: We report here high rates of detection (50.8%, 31/61 pigs) of Torque teno sus virus (TTSuV) in kidneys of slaughter‐age, apparently healthy pigs on St. Kitts island, Lesser Antilles. TTSuV1 and TTSuVk2a were detected in 23 (37.7%) and 13 (21.3%) pigs, respectively, including mixed infection in five animals. By nucleotide sequence identities and phylogenetic analysis, significant genetic diversity was observed among both TTSuV1 and TTSuVk2a on St. Kitts, with TTSuVk2a showing higher genetic diversity than TTSuV1. Fourteen (45.2%) and 10 (32.2%) of the TTSuV infected pigs tested positive for porcine circovirus type 2 (PCV2) and porcine parvovirus (PPV), respectively, revealing high rates of co‐infection of TTSuV with PCV2 and PPV. This is the first report on detection and genetic diversity of TTSuV from the Lesser Antilles. Also, PCV2 and PPV were detected for the first time in the Lesser Antilles. Considering the impact of pig farming on the regional livestock economy, the increasing demand for local pork and lack of information on emerging and re‐emerging porcine viruses in the Lesser Antilles, the present findings have important implications on swine health.